SOCIAL PROTECTION IN UZBEKISTAN IS A PRIORITY AREA OF STATE POLICY (Scientific journal of the Fergana State University, 2024)
This article reflects the state policy of social protection at the highest level in our country and analyzes the fact that fair social policy is considered one of the priorities in the development strategy of New Uzbekistan for the next five years from the side of our president. In addition, the article highlights the importance of normative legal documents in the Republic of Uzbekistan on social protection.